A multi-parameter investigation of elite archery: distinguishing individual and shared performance strategies during the aiming and follow-through phases - Jacquot, R.; Ben Mansour, K.; Bouillet, K.; Jehl, J.-P.; Gauchard, G. (Frontiers in Sports and Active Living, 2025)
Introduction: Archery accuracy relies heavily on the aiming and follow-through phases, during which factors such as muscle activation, postural control, and drawing arm movement play key roles. This study aims to assess whether these performance determinants in high-level archery are consistent across athletes or reflect individual-specific strategies.